Chitosan as A Plant Pathogen Control Agent: A Review - Lidi, Maria Waldetrudis; Cahyaningrum, Hermawati -; Uge, Emerensiana (Universitas Panji Sakti, 2024)
Pathogen attacks can cause decreased yields, even crop failure. Proper control can suppress pathogens' development and maintain yields. The concept of integrated pest management emphasizes the application of several techniques, one of which is the use of organic products as vegetable pesticides. Chitosan is a natural product obtained from crustacean shells or skins which can be used in various fields, including agriculture. Indonesia is one of the countries producing raw products from crustacean animals (shrimp, crab, lobster, and squid). This also has an impact on the amount of shell or skin waste produced. The processing of crustacean animal skin waste into chitosan can go through several stages, namely deproteinized, demineralization, and deacetylation. Chitosan application can be done by seed treatment, foliar spraying, soil application, and post-harvest products. The mode of action of chitosan against pathogenic fungi is binding to phospholipids in the plasma membrane of fungal cells, causing changes in hyphal morphology, degrading fungal enzymes, increasing levels of phenolics, sugar, and proline, and activating antimicrobial compounds and defense-related enzymes. The modes of action against pathogenic bacteria are interfering with gene expression, causing cell lysis, destroying bacterial biofilms, increasing defense enzyme activity, inducing systemic resistance, damaging and changing cell membranes, and causing cell wall permeability. The mode of action against pathogenic viruses is to increase the expression of genes related to defense, inhibit systemic viral multiplication and hypersensitivity response. The utilization of chitosan products is very important to study, especially in suppressing the use of chemical products and maintaining ecosystem sustainability.